Insights and Ideas T.3 = Luyện kỹ năng đọc tiếng Anh - Ackert, Patricia; Nebel, Anne L. (Tp.HCM : Nxb Trẻ, 2000)
The book has 25 short reading and many kinds of activities. It can help learners to read, talk, write about interesting topics and to improve their reading skills.
Keywords: English language; Reading; Practice skills; English language -- Practice Skills; English language -- Study and teaching